Current and next-generation formulation strategies for inactivated polio vaccines to lower costs, increase coverage, and facilitate polio eradication. Issue 7 (30th December 2022) - Kumar, Prashant; Bird, Christopher; Holland, David; Joshi, Sangeeta B.; Volkin, David B.
ABSTRACT: Implementation of inactivated polio vaccines (IPV) containing Sabin strains (sIPV) will further enable global polio eradication efforts by improving vaccine safety during use and containment during manufacturing. Moreover, sIPV-containing vaccines will lower costs and expand production capacity to facilitate more widespread use in low- and middle-income countries (LMICs). This review focuses on the role of vaccine formulation in these efforts including traditional Salk IPV vaccines and new sIPV-containing dosage forms. The physicochemical properties and stability profiles of poliovirus antigens are described. Formulation approaches to lower costs include developing multidose and combination vaccine formats as well as improving storage stability. Formulation strategies for dose-sparing and enhanced mucosal immunity include employing adjuvants (e.g. aluminum-salt and newer adjuvants) and/or novel delivery systems (e.g. ID administration with microneedle patches). The potential for applying these low-cost formulation development strategies to other vaccines to further improve vaccine access and coverage in LMICs is also discussed.